An Online Investigation of Knowledge and Preventive Practices in Regard to COVID-19 in Iran - Mohammad Reza Heydari; Hassan Joulaei; Nooshin Zarei; Mohammad Fararouei; Zahra Gheibi (SLACK Incorporated, 2021)
BACKGROUND: Until now, there was no available study on the knowledge and practice of the people of Iran with regard to the coronavirus disease 2019 (COVID-19) pandemic. OBJECTIVE: This study aimed to investigate the knowledge and preventive practices of Iranians toward the COVID-19 pandemic. METHODS: This is a cross-sectional study of 925 people who completed an online questionnaire in March 2020. The study used 21 and 14 questions, respectively, to assess the knowledge and preventive practices of the population in regard to COVID-19. Cronbach's alpha was 0.75 for the knowledge scale and 0.71 for the practice scale. To determine the importance of each independent variable in explaining the participant's practice, a multiple regression model was applied. KEY RESULTS: The results indicated a moderate level of knowledge and preventive practices in regard to COVID-19 in most of the respondents (56.8% and 56.5%, respectively). According to the multiple regression analysis, knowledge showed the highest effect on the practice of the participants (β = 0.479). The determination coefficient for the model (R2 = 0.509) also showed approximately 51% of the variance in practice was explained by gender, occupational status, knowledge, cost of hand sanitizer, and the belief in the effectiveness of using such necessities. CONCLUSIONS: Acceptable rates of knowledge and practice were observed in most Iranians. However, approximately 10% of the participants were unaware of the effective measures for preventing the infection, which can cause active transmission of the virus. In addition to considering the importance of high community awareness in prevention and isolation measures, the government should provide disinfectants and other materials at a low price to reduce the transmission, as this may lead to effective practice to break the chain of transmission of COVID-19.